Calculus and analytic geometry - Riddle, Douglas F. (Belmont, California : Wadsworth Publishing Company, 1979)
As in the previous editions, we have striven to present calculus in a way that is as easy as possible for the student to understand as we as easy for the instructor to present.
Plane Analytic Geometry -- Equations of Lines and Circles -- Functions -- The derivative -- Curve Sketching -- Further Applications of the Derivative -- The Integral Vectors in the Plane -- Conic Sections -- Limits and Continuity: A Geometric Approach -- Trigonometric Functions -- Exponents, Logarithms, and Hyperbolic Functions -- Parametric Equations -- Polar Coordinates -- Methods of Integration -- Further Applications of the Integral -- Limits and Continuity: The Epsilon-Delta Approach -- Indeterminate Forms -- Infinite Series -- Solid Analytic Geometry -- Partial Derviatives -- Multiple Integrals -- Line and Surface Integrals.
Includes index.
Keywords: CALCULUS